The impact of capital adequacy, efficiency and liquidity on the profitability of private banks: A comparative study between Islamic and traditional banks working in Syria (Journal of Hama University, 2022)
The aim of this research is to study the impact of capital adequacy, efficiency and liquidity on the profitability of private banks working in Syria and to compare the results between Islamic and traditional banks during the period 2011-2020.The study used ROE as a dependent variable. While the ratio of equity to total assets, the ratio of operating expenses to total assets and the ratio of ready liquidity were used as independent variables.The study used panel data. A set of statistical tests were performed to choose the appropriate model. For the traditional banks model a static panel data method was selected, and the restricted f test and hausman test were performed and the random effects model was selected. And for the Islamic banks model the dynamic panel data method was selected and the ARDL methodology was used. By that the study used both static and dynamic panel methods.The study concluded that there is a positive significant effect at 10% for all the previous variables on profitability of traditional. While there is a negative significant effect at 10% on profitability of Islamic banks. So this indicates that the traditional banks were better at managing internal determinants than Islamic ones.In the light of the results, the researchers recommend managing expenditures more effectively, shifting liquidity to various investments, and making better use of capital which contribute to increasing profits in Islamic banks.